Implementation of adaptive hysteresis current controller in grid tied multilevel converter with battery storage system - S. Karthikkumar; A. Sheela (Scientific Reports)
Abstract This research introduces an adaptive hysteresis current controller (HCC) integrated with a multilevel inverter (MLI) and a battery storage system (BSS), which improves real power injection accuracy and enhances performance during load fluctuations. Maintaining voltage stability is essential for delivering high-quality power, especially as networks become increasingly complex, particularly in distributed systems with nonlinear loads, necessitating innovative control strategies. The proposed controller demonstrates superior performance compared to traditional methods, overcoming the limitations of conventional inverters. Simulation results indicate that the total harmonic distortion (THD) of the system achieves 2.43%, representing a 52% improvement over standard HCC, and enhances system efficiency by 6.8%. Additionally, the adaptive HCC reduces current injection errors by up to 85%, indicating significant efficacy, with phase angle deviations of less than 1° from the grid voltage. This reduction in reactive power demands contributes to maintaining grid stability under controlled and stressed conditions. These results comply with IEEE Std 519-2014 and IEC 61000-3-2 standards, ensuring reliability. This novel adaptive technique ensures stable grid connection and improved power quality, particularly in residential and commercial areas with prevalent nonlinear loads. The findings confirm the method’s reliability and effectiveness for modern grids, even during dynamic and unstable conditions.